Adolescent friendly health services: perceptions and practice of medical professionals - E., Sujindra; A., Bupathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Introduction Adolescence is a period of intricacies, with a wide range of adolescent health problems, such as depression, eating disorders, drug and alcohol use, unplanned pregnancy, chronic illness, and suicide due to unfavorable social conditions and risk taking behaviors. Not many studies are there to assess problems related to providing health services to adolescents. Our study analyzed the views about perception and practice of adolescent health among doctors of the different groups of medical discipline. Methods: A total of 44 doctors, 12 from ayurveda, 10 from siddha, 10 from homeopathy and 12 from allopathy, were included in the study who filled in questionnaire containing 17 questions on perceptions and practice of adolescent health. Results: Response rate was 100%. Overall the doctors understanding on adolescent health was good. Majority of the doctors (90%) felt that adolescents are not comfortable in the present available setting to bring out their problems. Only 3 of our doctors had received formal training in adolescent health and are informed about adolescent friendly health services. There was no separate forum to render adolescent health services. Conclusions: Effectively planning, implementation and also evaluation of health programs in adolescent health is required to change attitude of adolescents, the health providers and also that of the setting where adolescents are addressed. Health professionals have their credibility towards adolescents, and the advice they give may be important for teenage behavior.